Trigger Tool in the active search for adverse drug reactions in a university (Research, Society and Development, 2023)
Medications are the most commonly used therapeutic tool in healthcare services; however, pharmacotherapy can present risks and potentially compromise the health and safety of patients. Pharmacovigilance is the instrument responsible for monitoring the use, effectiveness, and safety of medicines, as well as identifying adverse drug reactions (ADR) and working to prevent the occurrence of such events. The Trigger Tool methodology involves actively searching for adverse events using trigger drugs that indicate the possible occurrence of ADRs. The list of triggers developed by the Institute of Healthcare Improvement (IHI) was adapted for use in the institution. The search process was conducted retrospectively in medical records and aimed to complement the spontaneous reporting tool. This study aimed to conduct a survey and review of data from the active search for ADRs using the Trigger Tool methodology in a public university hospital located in the city of Ponta Grossa, PR. This is an observational and retrospective study, conducted over a period of eight months. A total of 56 possible ADRs were tracked, predominantly in elderly male patients. Hypersensitivity reactions with cutaneous manifestations and bleeding reactions were the most prevalent. The relative yield of the trigger drugs was calculated, and Naloxone, Flumazenil, and Protamine trackers showed better performance. The screening based on the Trigger Tool methodology proved valid in detecting ADRs, especially when using triggers that demonstrate good performance.